Service marketing mix in commercial banks of sri lanka - Ismail, M. B. M. (University of Jaffna, 2016)
Service Industry dominates other industries almost all over the World. Service industry includes finance, education, health and many other service industries. Financial services are important banking services. Different studies have different findings with respect to service marketing mix. Thus, this study aimed at knowing the factors of service marketing mix. This study collects data from 100 bank customers in two branches of bank of Ceylon in Batticaloa District. Data were collected from primary source i.e. questionnaire with 5 point - likert scale method. Results of the correlation values for service marketing mix elements such as product, place, promotion, price, people, process & physical evidence are 0.729, 0.663, 0.717,0.681, 0.711,0.491and 0.666 respectively. These values explain higher strength of association between service marketing mix elements. Study concludes that 7 service marketing mix such as product, price, place, promotion, people, process and physical evidence was used for initial factor analysis that revealed a total variance of 44.989%. However, final factor analysis that was conducted using promotion, people and physical evidence that explained around 65%
Keywords: Commercial banks; Service marketing mix, S; Sri lanka